(untitled) (Journal of Economic Research & Business Administration, 2016)
This article examines the concepts of «human capital» and «human potential ». The efficiency of using human potential in the Republic of Kazakhstan was estimated. The article provides recommendations for increasing the efficiency of using human potential. The effect that human potential has on economic growth is examined; national economy performance indicators of investments in human capital are calculated. Also, the theoretical and methodological foundations of human development in market economy conditions are explored. The influence of human capital on the competitiveness of economic systems has been analyzed. The effectiveness of investments in the development of Kazakhstan education has been evaluated. Priorities of development of the education system in the Republic of Kazakhstan were defined. Specific recommendations to improve the quality of the intellectual potential within the formation of a new educational concept have been given. The method of measuring human potential of society in the present day market conditions that allowing analyzing the efficiency of social investment in education is given. There is the quite clearly influence of the social sphere on development of the economy, which results in a direct relationship of basic socio-economic indicators.